Hypertension, Type 2 Diabetes Mellitus, and Stroke History in a 70-Year-Old Woman - Dasa Novita, Khuznita; Zulfikri Febriansyah, Muhammad (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Hypertension and type 2 diabetes mellitus are major contributors to cardiovascular disease in older adults, especially when combined with multiple risk factors. This report describes a 70-year-old woman with uncontrolled hypertension, newly diagnosed type 2 diabetes mellitus, obesity, and a previous ischemic stroke eight months prior. A holistic assessment using the Family Health Care Project (FHCP) framework was performed to identify factors contributing to poor control, including dietary habits, physical activity, medication adherence, sleep quality, and family support. Although the patient believed she had adopted a healthier lifestyle, evaluation revealed excessive carbohydrate intake, irregular meal patterns, and inadequate sleep. Physical examination showed a BMI of 35.9 kg/m² and blood pressure of 166/76 mmHg, while laboratory results indicated elevated fasting glucose. Family assessment demonstrated strong emotional support but limited health literacy. Management focused on lifestyle counseling, medication review, stopping unnecessary allopurinol, and strengthening family involvement. Follow-up home visits showed improved understanding, better eating habits, and improved blood pressure control. This case highlights the importance of addressing multiple risk factors through a family medicine approach to optimize chronic disease management in elderly patients.